THE EFFECT OF CAPITAL STRUCTURE, LIQUIDITY, AND PROFITABILITY ON COMPANY VALUE WITH COMPANY SIZE AS A CONTROL VARIABLE - Novi Pujiati; Dian Indriana Hapsari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to determine the effect of capital structure, liquidity, and profitability on the value of mining companies listed on the Indonesia Stock Exchange for the period 2019–2021, with company size as the control variable. The research was conducted using quantitative techniques. Share prices and financial statements of mining companies from 2019 to 2021 are the data sources. Used multiple linear regression to analyze the data. According to the study findings, company size has a sizable positive impact on company value as assessed by PBV for mining industry companies for the period 2019–2021. Profitability is measured by ROA, and part of the capital structure is determined by the debt equity ratio. Meanwhile, liquidity is measured by the current ratio, which has no significant negative effect on company value, measured by PBV in mining sector companies for the 2019-2021 period. Prove simultaneously that company size has a significant positive effect on company value as measured by PBV in mining sector companies listed on the Indonesia Stock Exchange for the 2019–2021 period. Firm size is measured by the debt equity ratio, liquidity is measured by the current ratio, profitability is measured by ROA, and company size is measured by the company.